Increasing sorghum yields for smallholder farmers in Mali: the evolution towards a context-driven, on-farm, gender-responsive sorghum breeding program - Isaacs, Krista; Weltzien-Rattunde, Eva; Some, Tiare Hermann Williams; Abdoulaye Diallo; Bocar Diallo; Mamourou Sidibé; vom Brocke, Kirsten; Bakary Samake; Nebié, Baloua; Weltzien-Rattunde, Henry Frederick (Frontiers Media, 2024)
This case study explores a decades long evolution towards a gender-responsive sorghum breeding program in Mali. With known disparities in men and women’s access to the resources that improve agricultural productivity and evidence that gender roles and responsibilities shape knowledge and preferences about varieties, there is need for methods that support gender-responsive processes in plant breeding programs. Gender-sensitive and gender-responsive approaches in plant breeding may increase varietal options available to diverse end-users, increase adoption, and limit negative impacts on vulnerable populations. We assess a participatory plant breeding program in Mali to identify determinants of gender-responsive breeding programs. The analysis uses a case study methodology that draws upon project reports, theses, articles, and experiential knowledge to understand how the sorghum breeding program transitioned over time. This case study details (a) more than a decade of sorghum breeding activities and research that led to (b) the inclusion of women in participatory plant breeding, culinary tests, and large-scale participatory selection in on-farm trials, reaching hundreds of women each year and (c) iterative co-learning processes to develop preferred sorghum varieties and increase sorghum yields on men and women’s fields. Analyses indicated that collaborations among many institutions on-farm with community actors, research across various disciplines such as agronomy and social sciences, context-specific breeding, and long-term funding were essential to increasing gender sensitivity and responsive in the breeding efforts.